Analisis Motivasi, Kompetensi, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Kinerja Dokter Gigi Pada Rumah Sakit Gigi Dan Mulut Institut Ilmu Kesehatan Bhakti Wiyata (RSGM IIK Bhakta) Kediri - Karina, Asa; Suwasono, Edi; Sumarji, Sumarji (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
In the current era of globalization, there is increasing public demand for dental and oral health services. Along with the increasing demand for dental and oral health services, many new hospitals are present, as well as with the increasing demand for medical personnel, especially dentists. The large number of hospitals present encourage consumers to be selective in choosing health services with good quality. This problem causes competition among health service providers. For this reason, companies are required to carry out dynamic changes, so that they can remain competitive and survive with other companies. One of the strategies that must be carried out by the company is to pay attention to its human resources. Human resources play a very important role for the company, because human resources are a driving force in the company's activities in order to achieve the strategic goals planned beforehand. Coupled with a decrease in the number of patient visits in the last 7 months. Human resources are the main key in solving this problem. This research is a quantitative research. The population used was permanent dentists and the sample used was total sampling (all populations were sampled), totaling 58 permanent dentists. This research was analyzed using SPSS 25. The results of this research are 1) Motivation, competence, work environment and job satisfaction simultaneously influences dentist performance 2) Motivation partially influences dentist performance 3) Competence partially influences dentist performance 4) Work environment partially influences dentist performance 5) Job satisfaction partially influences dentist performance.